Inhibition of sodium glucose cotransporter 2 (SGLT2) delays liver fibrosis in a medaka model of nonalcoholic steatohepatitis (NASH). Issue 4 (15th February 2019) - Goto, Ryo; Kamimura, Kenya; Shinagawa‐Kobayashi, Yoko; Sakai, Norihiro; Nagoya, Takuro; Niwa, Yusuke; Ko, Masayoshi; Ogawa, Kohei; Inoue, Ryosuke; Yokoo, Takeshi; Sakamaki, Akira; Kamimura, Hiroteru; et al.
Abstract : The rise in the incidence of nonalcoholic steatohepatitis (NASH) has necessitated the development of an effective prevention methodology. An antidiabetic drug, belonging to the group of sodium glucose cotransporter 2 (SGLT2) inhibitors, has been tested for its therapeutic effect on NASH; however, no studies to date have demonstrated the preventive effect of an SGLT2 inhibitor on the histological progression of steatosis and fibrosis in a sequential manner in animal models. In the present study, we examined the effect of the SGLT2 inhibitor, tofogliflozin (Tofo), on NASH liver tissue using medaka as an animal model, maintaining a feeding amount and drug concentration in all animal bodies. We generated a medaka NASH model by feeding d‐rR/Tokyo medaka a high‐fat diet and administered Tofo by dissolving the drug directly in the water of the feeding tank. Thereafter, the effects of Tofo on body weight (BW), liver weight, hepatotoxicity, fatty infiltration, and fibrotic changes in the liver were examined. We report here that SGLT2 is expressed in medaka fish and that Tofo inhibits the accumulation of fatty tissue and delays the progression of liver fibrosis in the medaka NASH model by inhibiting increases in blood sugar, serum lipids, and transaminase, irrespective of changes in BW. These results suggest that Tofo is effective for treating NASH and that the medaka model may be useful for developing new therapeutic drugs for this disease. Abstract : Here, we demonstrate that Sglt2 is expressed in medaka kidney and that treatment with sodium glucose cotransporter 2 inhibitor (SGLT2I) ameliorates steatosis and fibrosis in a medaka model of nonalcoholic steatohepatitis (NASH). Our results suggest an anti‐NASH effect of a SGLT2I drug, which may help facilitate the development of new therapeutic drugs.